Artificial intelligence and the planning task - Peter Ache (PlaNext)
The editors of this special issue invited me to reflect on the planning task and, given the 10th anniversary of plaNext, to provide an outlook for the next ten years or more regarding urban futures, all in connection with artificial intelligence (henceforth, AI). A fine call to develop a piece of speculative future, seasoned with armchair evidence from actual debates about cities, futures, and artificial intelligence. I will do so in nine movements, starting by briefly addressing what the urban is made of, a clarification which is essential for our view on the makings of AI. Then I will look at AI proper, well not as an expert, which I am certainly not, but rather like what I find interesting about AI and what is supposedly confronting us in the planning context. Finally, a short outlook will be done inviting the renowned science fiction author Phil K. Dick for a comment on the future and the urban.